2021
DOI: 10.1186/s12902-021-00679-9
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of endoscopic transsphenoidal surgery for Cushing's disease

Abstract: Background Transsphenoidal surgery (TSS) to resect an adrenocorticotropic hormone (ACTH)-secreting pituitary adenoma is the first-line treatment for Cushing’s disease (CD), with increasing usage of endoscopic transsphenoidal (ETSS) technique. The aim of this study was to assess remission rates and postoperative complications following ETSS for CD. Methods A retrospective analysis of a prospective single-surgeon database of consecutive patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Recent studies have reported remission rates of 74–82% after first operations [ 12 , 34 ]. The recurrence rates reported previously varied between 3% and 66% [ 5 , 12 , 34 ]. However, the duration of follow-up differed among the studies.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported remission rates of 74–82% after first operations [ 12 , 34 ]. The recurrence rates reported previously varied between 3% and 66% [ 5 , 12 , 34 ]. However, the duration of follow-up differed among the studies.…”
Section: Discussionmentioning
confidence: 99%
“…Literature evidence suggests that pituitary surgery is widely considered the first-line treatment in CD management, even considering that an optimal success rate is reported especially among centers of excellence and may vary according to different factors, including patients’ characteristics, and preoperative visualization, size, and location of the pituitary tumor, as well as the surgeon experience [ 10 , 16 , 22 , 23 ]. Consistent with this evidence, Delphi panel outcomes highlighted that the CD surgical management has some limitations (81% of agreement), mainly related to patients’ characteristics (refusal of surgery, comorbidities increasing the anesthesiologic/surgical risk, non-accessibility to all patients [ 15 ]), and to surgery issues, such as invisible or small size tumors, as well as unfavorable location or extrasellar expansion of the pituitary tumor.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to different study designs (sample size and follow-up time), tumor characteristics (invasiveness, tumor size, and localization), surgical experience, and adjuvant therapies, this may be due to the lack of a uniform consensus for the definition of remission, including immediate and delayed remission [ 12 , 13 ]. For example, a low (<50 nmol/L, 100 nmol/L, or 138 nmol/L) or normal morning serum cortisol level within 3, 4, or 7 days after surgery, clinical symptom disappearance, normal or decreased UFC levels over the past 24 h, the success of a low-dose dexamethasone test, or a combination of two or more aforementioned criteria was used to define tumor remission [ 4 , 11 , 14 , 15 , 16 , 17 ]. The criteria for CD recurrence seemed to be relatively consistent, including an increase in serum cortisol level, an increase in night salivary cortisol level, and/or an increase in 24 h UFC level, with clinical hallmarks reviewed by Qiao [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Random cortisol level evaluations were performed, and cortisol replacement treatment was initiated until the HPA axis was restored when patients exhibited signs or symptoms of hypocortisolemia. Immediate remission was defined as a morning serum cortisol level of <138 nmol/L (5 µg/dL) or UFC level of <28–56 nmol/day (10–20 μg/dL) within 7 days after surgery [ 4 , 5 ]. Because a progressive decline in cortisol level to a normal or low level within three months after surgery has been identified in previous studies [ 6 , 7 , 8 ], patients without any additional therapy had a delayed remission with a low or normal morning serum cortisol level with a resolution of clinical features during the first three months of the follow-up period after resection.…”
Section: Methodsmentioning
confidence: 99%